PROGRAMMING GENES IN BRAIN AND PROBLEM OF SOCIAL BEHAVIOR ОF MAN - B. B. Fuks (Бюллетень сибирской медицины, 2013)
Transcription factors programmed genes of brain cells. Then proteins synthesized form long term memory. Two genes of hormone vasopressin receptor – genes of altruism / selfishnessand one oxytocin receptor gene provide social recognition, memory and behavior. Human population divided into three groups: homozygous altruists, homozygous egoists and heterozygous group containing both vasopressin genes. Behavior genes programming in the last group occurs within the first two weeks of life. Negative programming of masses of people in this group could be the cause of social disasters in the twentieth century.